Обчисліть √1 + √2 ∙ √3 − 2√2.


Обчисліть √1 + √2 ∙ √3 − 2√2.

minpro minpro    1   23.08.2020 00:39    0

Ответы
Даниссиммо1 Даниссиммо1  15.10.2020 16:11

1

Объяснение:

\sqrt[3]{1+\sqrt{2} } *\sqrt[6]{3-2\sqrt{2} } =\sqrt[6]{(1+\sqrt{2}) ^{2}*(3-2\sqrt{2}) }=\\\\ =\sqrt[6]{(1+2\sqrt{2}+2)(3-2\sqrt{2}) } =\sqrt[6]{(3+2\sqrt{2})(3-2\sqrt{2}) }= \\\\=\sqrt[6]{9-8} =\sqrt[6]{1}=1\\

ПОКАЗАТЬ ОТВЕТЫ
LadnoOK LadnoOK  15.10.2020 16:11

под вторым корнем шестой степени (1-√2)²=1+2-2√2=3-2√2

его можно переписать так ∛(√2-1)

тогда окончательно ∛(1+√2)*∛(-1+√2)∛(-1+2)=1

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра